Avoidance Behavioral Difference in Acquisition and Extinction of Pain-Related Fear - Nishi, Yuki; Osumi, Michihiro; Nobusako, Satoshi; Takeda, Kenta; Morioka, Shu (Frontiers in Behavioral Neuroscience, 2019)
Fear of movement-related pain leads to two types of avoidance behavior: excessive avoidance and pain-inhibited movement. Excessive avoidance is an absence of movement by fear, and pain-inhibited movements involve a change in motor behavior for the purpose of protecting the painful part. Here we sought to clarify the acquisition process and adaptation of fear for each avoidance behavior. The 31 female and 13 male (age 20.9±2.1 years) subjects could decide persistent behaviors; approach with an intense pain stimulus, pain-inhibited movement with weak pain stimulus, or excessive avoidance with no pain in acquisition and test phases. In the subsequent extinction phase, the pain stimulus was omitted. Subjects were divided into approach group (n=24), pain-inhibited movement group (n=10), and excessive avoidance group (n=10) by cluster analysis. The response latencies in approach and pain-inhibited movement groups were not affected by conditioned pain. Excessive avoidance group's subjects exhibited delayed response latencies, and their high fear responses, remained in the acquisition, test, and extinction phases. In addition, the excessive avoidance group showed high harm avoidance and high trait anxiety. This study demonstrated that differences in pain-related avoidance behaviors are affected by psychological traits. Pain-related excessive avoidance behavior indicated a maladaptive fear, but pain-inhibited movement did not.